2011
DOI: 10.3802/jgo.2011.22.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Differences in perioperative outcomes after laparoscopic management of benign and malignant adnexal masses

Abstract: ObjectiveTo compare the feasibility and safety of the laparoscopic management of adnexal masses appearing preoperatively benign with those suspicious for malignancy.MethodsRetrospective study of 694 women that underwent laparoscopic management of an adnexal mass.ResultsLaparoscopic management of an adnexal mass was completed in 678 patients. Six hundred and thirty five patients had benign pathology (91.5%) and 53 (7.6%) had primary ovarian cancers. Sixteen patients (2.3%) were converted to laparotomy; there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
3
7
1
3
Order By: Relevance
“…The results showed that patients with malignancy or metastasis were signi cantly older and had a longer duration of surgery and intra-operative complications. These results are consistent with the results of the study by Gad et al, which reported higher rate of complications and longer operative time in patients with borderline/malignant adnexal mass, compared to benign group undergoing laparoscopic treatment (20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that patients with malignancy or metastasis were signi cantly older and had a longer duration of surgery and intra-operative complications. These results are consistent with the results of the study by Gad et al, which reported higher rate of complications and longer operative time in patients with borderline/malignant adnexal mass, compared to benign group undergoing laparoscopic treatment (20).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, they reported higher rate of conversion to open, blood loss, and duration of hospital stay (20), which was not observed in our study. Other studies have also con rmed the superiority of laparoscopy vs. laparotomy for treatment of ovarian cancers (21,22), as well as comparable accuracy of staging of laparoscopy vs. laparotomy and comparable survival rates (23,24), while the results of the present study suggested higher complication rates in large tumors.…”
Section: Discussioncontrasting
confidence: 90%
“…Mohamad S. Gad and James H. Liu, in their paper, said that LPS was used mainly for benign masses, instead LPT was used mainly for malinant and borderline masses, these results are comparable to our results [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…With the rapid evolution of laparoscopic techniques and instruments, LAVH has become one of the most common procedures for hysterectomy (2). Such laparoscopic surgeries have advantages, such as shorter hospital stays, faster recovery times and better cosmetic outcomes (3,4).…”
Section: Introductionmentioning
confidence: 99%